Modelling Seismically Induced Mesothermal Goldfields along the Deep-Rooted Cadillac-Larder Lake Fault, Abitibi, Canada - Pierre Bedeaux; Silvain Rafini; Pierre Pilote; Réal Daigneault (Geofluids)
Gold deposits are not uniformly distributed along major faults due to complex (and long-debated) interactions between seismicity, hydrothermalism, and structural heterogeneities. Here, we use static stress modelling (SSM) to quantitatively investigate these interactions, by exploring the role of Cadillac-Larder Lake Fault (CLLF) Archean seismicity in the genesis of the regional goldfields. Various rheological factors are evaluated for optimizing the models’ ability to reproduce known gold occurrences, regarded as the fossil primary markers of synkinematic hydrothermal systems. We propose that the marked structural heterogeneities of the CLLF induced persistent seismic segmentation and recurrent ruptures of the same fault windows that arrested on robust node points. These ruptures favour repeated occurrences of seismically triggered hydrothermalism along long-existing fluid pathways having an enhanced permeability and iterative ore formation into supracrustal discharge zones by means of episodic drops and build-ups of pressure. Two-dimensional SSM permits the predictive mapping of these high-potential zones. These modelled zones correlate positively with the actual observed gold distribution. We demonstrate that (1) the ruptures along the Joannes Segment arresting on the Davidson Fault and Lapa’s bend can explain the occurrence and location of the Rouyn and Malartic goldfields; (2) the models’ validity is improved by implementing regional geological constraints; and (3) the distant gold occurrences from the CLLF, including the Bourlamaque field, can be explained by doublet seismic events along the Rivière-Héva and Lapause subsidiary faults. Our results provide new perspectives from a fundamental standpoint and for exploration purposes.